Teaching Money Literacy in a Positive Youth Development Program: The Project P.A.T.H.S. in Hong Kong - Tak Yan Lee; Ben M. F. Law (The Scientific World Journal)
In view of the high impact of materialistic orientation among children and adolescents, financial educational programs are provided as preventive measures. Without a clear framework, it is impossible to evaluate these programs. The goals of this paper are threefold. Firstly, the phenomena related to adolescent materialistic orientation and its associated problems in Hong Kong are examined. Secondly, the concept of financial education as a preventive measure is reviewed. Both board and narrow definitions of money literacy are examined. A framework on money literacy for children and adolescents as a founding stone for financial education is proposed. The framework finds its support from a typology proposed by the authors and results from an integration of research findings on dimensions of the concepts of money and success. Finally, curriculum units for Grades 7 to 9 students in a positive youth development program (the Project P.A.T.H.S.) are developed using the framework.